Vibratory Angioedema Subgroups, Features, and Treatment: Results of a Systematic Review - Kanokvalai Kulthanan (2022)
Background: Vibratory angioedema (VA) is a subtype of chronic inducible urticaria that manifests with erythematous wheals or angioedema after skin exposure to vibration. Because the condition is rare, the available information is limited. Objective: To systematically review the clinical manifestations and treatment options of VA. Methods: Relevant literature published until August 2020 was searched using the terms “vibratory urticaria,” “vibratory angioedema,” “vibratory-induced angioedema,” and “vibratory-induced urticaria.” Preferred Reporting Items for Systematic Reviews and Meta-analysis recommendations were applied to this systematic review. Results: On the basis of review of 22 studies (16 case reports, 4 case series, and 2 cohort studies) that had a combined total of 83 patients, we propose that VA be classified as hereditary VA (33.7%) and acquired VA (66.3%). Vibration-induced itching was frequent in both subgroups. Patients with hereditary VA more commonly had wheals and systemic symptoms, whereas patients with acquired VA more frequently had angioedema, burning, pain, or tingling. Although many VA treatments are used, there is little information on their efficacy. Most patients do not achieve complete control. Conclusions: The novel VA classification proposed could help clinicians with the diagnostic workup of patients with VA. Because of the paucity of reported cases, firm recommendations for the treatment of VA are currently not possible. For patients with acquired VA, we suggest second-generation H1-antihistamines as the first-line treatment. Controlled therapeutic trials are needed and should be performed.